PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, MOTIVASI KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN KUD PAKIS KABUPATEN MALANG - Zulkifli Zulkifli; Hadi Sunaryo; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research is based on interesting events about the condition of the Village Unit Cooperative as one of the means to develop the economy of rural communities in Indonesia that use family principles. This study aims to determine the effect of work environment, work discipline, work motivation, and work stress on employee performance at KUD Pakis, Malang Regency. By using the explanatory reseach method by distributing questionnaires to all employees it has been found that the work environment, work discipline, work motivation, and work stress have a positive effect on employee performance and this becomes the basis of a Village Unit Cooperative to correct every variable that has been careful.Keywords: Work Environment, Work Discipline, Work Motivation, Job Stress, Employee Performance